RELEVANSI STABILITAS KEUANGAN BANK TERHADAP RISIKO INVESTASI DAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MEDIASI - Sutandijo Sutandijo; Listya Sugiyarti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to test and analyze empirically the relevance of bank financial stability (STAB) to bank stock investment risk (RISK), with dividend policy (DIV) as a mediating variable; and bank company size (SIZE), status of state-owned enterprises (BUMN), and regionally-owned enterprises (BUMD) as control variables. The population in this study are national commercial banks consisting of private banks and BUMN/BUMD banks listed on the Indonesia Stock Exchange for the 2011-2020 period. Using a purposive sampling method, the number of bank companies sampled in this study was 16 bank companies with a total of 160 observations of financial report data (over a 10 year period). In this study, multiple linear regression analysis techniques and Ordinary Least Square models were used with data processing using eviews 9 software. The results of this study indicate that simultaneously STAB, DIV, and the control variables SIZE, BUMN, BUMD have a significant effect on RISK. Meanwhile, partially, STAB and SIZE have a negative effect on RISK in bank stocks. In addition, STAB has a positive effect on DIV, but DIV has no effect on RISK, so it can be concluded that dividend policy is proven not to mediate the effect of financial stability on investment risk in bank stocks.